Pengaruh Green Accounting, Profitabilitas, Leverage, dan Ukuran Perusahaan terhadap Agresivitas Pajak - Safitri, Silvia Nur; Indah Rahayu Lestari (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
This study aims to determine the effect of green accounting, profitability, leverage, and company size on tax aggressiveness. The population in this study is energy sector companies listed on the Indonesia Stock Exchange for the financial reporting period 2020-2024. The sampling technique used in this study is purposive sampling, and a sample of 35 companies was obtained. The analysis technique used is multiple linear regression analysis using SPSS version 22.0. The results of this study indicate that green accounting has a positive and significant effect on tax aggressiveness, profitability has a positive and significant effect on tax aggressiveness, leverage does not have a significant effect on tax aggressiveness, and company size does not have a significant effect on tax aggressiveness. The results show that green accounting and profitability have a positive and significant influence on tax aggressiveness, while leverage and firm size do not significantly influence tax aggressiveness. These findings provide insight that companies with a concern for environmental impacts tend to implement more aggressive tax policies, and that more profitable companies have an incentive to optimize their tax management.